Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s12970-018-0208-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lemon verbena extract (Recoverben®) supplementation on muscle strength and recovery after exhaustive exercise: a randomized, placebo-controlled trial

Abstract: BackgroundExhaustive exercise causes muscle damage accompanied by oxidative stress and inflammation leading to muscle fatigue and muscle soreness. Lemon verbena leaves, commonly used as tea and refreshing beverage, demonstrated antioxidant and anti-inflammatory properties. The aim of this study was to investigate the effects of a proprietary lemon verbena extract (Recoverben®) on muscle strength and recovery after exhaustive exercise in comparison to a placebo product.MethodsThe study was performed as a random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 39 publications
0
25
0
1
Order By: Relevance
“…This review outlined a wide assortment of ingredients, functional foods, and dietary supplements that have been shown to affect EIMD-related outcomes, with varying levels of success. In addition to the topics covered in the present review, many emergent nutritional and supplementation strategies have not been fully explored, including black tea-sourced polyphenols [161], blueberries [162], chondroitin sulfate [163], high chlorogenic acid coffee [164], fasting [165], garlic [166], leucine metabolites such as HICA [167], lemon verbena [168], lychee [169], mate tea [170], pequi fruit [171, 172], quercetin [173], saffron [174], selenium [175], sesame [176], spinach [177], and tomato juice [178, 179]. Future research in these nascent areas may shed new light on potential treatment options for EIMD.…”
Section: Discussionmentioning
confidence: 99%
“…This review outlined a wide assortment of ingredients, functional foods, and dietary supplements that have been shown to affect EIMD-related outcomes, with varying levels of success. In addition to the topics covered in the present review, many emergent nutritional and supplementation strategies have not been fully explored, including black tea-sourced polyphenols [161], blueberries [162], chondroitin sulfate [163], high chlorogenic acid coffee [164], fasting [165], garlic [166], leucine metabolites such as HICA [167], lemon verbena [168], lychee [169], mate tea [170], pequi fruit [171, 172], quercetin [173], saffron [174], selenium [175], sesame [176], spinach [177], and tomato juice [178, 179]. Future research in these nascent areas may shed new light on potential treatment options for EIMD.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, multidisciplinary research has been addressed to develop phenolic ingredients against inflammation which could be a practical tool for healthcare providers. Indeed, there are many commercial nutraceuticals attained from different natural sources which have been tested in induced inflammation models with promising results and some of them are listed in Table 2 [58].…”
Section: Inflammation and Phenolic Compoundsmentioning
confidence: 99%
“…In this scenario, Buchwald-Werner et al, tested a new lemon verbena extract called Recoverben ® on active people. The outcomes revealed that 400 mg/day of L. citriodora extract resulted in significantly less muscle strength loss and an enhancement of muscle recovery after exhaustive exercise [58].…”
Section: Functional Ingredients Based On Phenolic Compounds With Amentioning
confidence: 99%
“…In our study, the high intake of verbena EO by the delayed chicks and its low intake by the control chicks during the 6 days after the negative postnatal experience suggest that delayed chickens may select verbena EO for its properties. The antioxidant, anti-inflammatory, sedative, and digestive effects of lemon verbena are well reported in in vitro and in vivo studies and more recently the beneficial effect of this EO on muscle damage after exhaustive exercise was described (Buchwald-Werner et al, 2018). The exposure of the chicks to the combination of feed and water deprivation, temperature changes, and unpredictable shaking may explain their choice to consume verbena EO.…”
Section: Discussionmentioning
confidence: 96%